2022
DOI: 10.1158/0008-5472.can-22-0717
|View full text |Cite
|
Sign up to set email alerts
|

DLGAP1-AS2–Mediated Phosphatidic Acid Synthesis Activates YAP Signaling and Confers Chemoresistance in Squamous Cell Carcinoma

Abstract: Squamous cell carcinomas (SCC) constitute a group of human malignancies that originate from the squamous epithelium. Most SCC patients experience treatment failure and relapse and have a poor prognosis due to de novo and acquired resistance to first-line chemotherapeutic agents. To identify chemoresistance mechanisms and explore novel targets for chemosensitization, we performed whole-transcriptome sequencing of paired resistant and parental SCC cells. We identified DLGAP1 antisense RNA 2 (D-AS2) as a crucial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 71 publications
(80 reference statements)
2
17
0
Order By: Relevance
“…Recent studies also reported the upregulation and prognostic value of DLGAP1-AS2 in several cancer types. Similar tumor-promoting functions have also been observed in multiple cancer types, including rectal cancer [ 19 26 ]. For example, a recent study conducted by Zeng et al reported that DLGAP1-AS2 promotes the radioresistance in rectal cancer stem cells through regulating the E2F1-CD151 axis [ 27 ].…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies also reported the upregulation and prognostic value of DLGAP1-AS2 in several cancer types. Similar tumor-promoting functions have also been observed in multiple cancer types, including rectal cancer [ 19 26 ]. For example, a recent study conducted by Zeng et al reported that DLGAP1-AS2 promotes the radioresistance in rectal cancer stem cells through regulating the E2F1-CD151 axis [ 27 ].…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, we detected the protein level of FTO in the parental and chemoresistant ESCC cell lines previously established. 27 The results showed that FTO protein expression was upregulated in both chemoresistant cell lines compared with their preprint (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Fto Stabilizes Link-a and Correlates With Chemoresistancementioning
confidence: 99%
“…Then, to further identified FTO-regulated lncRNAs, we depleted or overexpressed FTO in two ESCC cell lines and detected the expression levels of 14 annotated ncRNAs that were previously shown to be significantly upregulated in chemoresistant ESCC cell lines compared with the parental cell lines. 27 The expression of four ncRNAs (TTLL3, LINC00663, PRSS30P and CETN4P) were too low to be detected by real-time quantitative PCR (RT-qPCR).…”
Section: Fto Stabilizes Link-a and Correlates With Chemoresistancementioning
confidence: 99%
See 2 more Smart Citations